Making thirsty cities sustainable: A nexus approach for water provisioning in Quito, Ecuador. (15th October 2022) - González-Zeas, D.; Rosero-López, D.; Muñoz, T.; Osorio, R.; De Bièvre, B.; Dangles, O.
Abstract: In view of accelerated climate change and urban demographics, balancing human and ecosystem needs for water resources is a critical environmental challenge of global significance. Since water, agriculture, health, and energy are inextricably linked, sustainable development goals (SDGs) actions in one policy area commonly have impacts on the others, as well as on the ecosystems that natural resources and human activities ultimately depend upon. Managing urban water supply systems therefore requires a nexus approach that integrates goals across sectors, reduces the risk that SDG actions will undermine one another, and ensures sustainable resource use. We developed a transdisciplinary methodological framework based on a Pareto frontier analysis to define the sustainable solutions of a multi-objective optimization among four competing criteria, water provision, water quality, energy cost, and biodiversity conservation. The study was applied to three mountainous headwater basins in the Ecuadorian Andes, which provide around 30% of Quito's total water supply. We found that an optimized management of water intake structures would meet current consumption needs while reducing the probability of emergence of water pathogens and limiting the impact on aquatic biodiversity by 30% and 9% respectively, without any increase in energy costs for pumping water from other sources. Nonetheless, under future scenarios of climate change and water demand, higher energy consumption, and therefore an increase in operating costs, would be needed to meet urban demand and preserve environmental conditions. Overall, the range of Pareto optimal water supply strategies across the water-health-energy-biodiversity nexus provides valuable information for decision makers and offers support for achieving sustainable management of water resources. Graphical abstract: Image 1 Highlights: We assess best case trade-offs among multiple criteria linked to a water supply system. A multi-objective optimization allows to define sustainable operating strategies. Sustainable management allows meet urban demand while reducing ecological impacts. Higher energy consumption will be needed to face future demand and climate change. A nexus approach provides valuable information for decision makers.